Praktik Perencanaan dan Pelaksanaan Pembelajaran Teks Berita di Kelas XI SMK: Studi Kasus Kualitatif - Herman Didipu; Sartika Djelema; Yunima I. Hasan; Ummul Khair; Juriyati Rajak (IEC: Journal of Educational Innovation, 2026)
Teaching news texts at the vocational high school (SMK) level faces unique contextual challenges, ranging from limited facilities and infrastructure, low student discipline and engagement,to differences in students’ economic backgrounds. This study aimsto describe the practices of planning, implementation, and the issuesthat need to be addressed in news text instruction in the 11th-grade SMK classroom.The study employed a qualitative approach with a single-case study design.The research subject was an Indonesian language teacher at SMK Negeri 2 Gorontalo. Data were collected through collaborative observation by a teamcomprising four observers, semi-structured interviews, and documentation. Data analysisfollowed the interactive model by Miles, Huberman, & Saldaña. The research resultsshowed that the teacher developed lesson plans by analyzing effective weeksbased on the academic calendar, designing a syllabus based on the Merdeka Curriculum, and developing systematic teaching modules. The implementationof instruction involved ice-breaking strategies, grade appreciation,the PBL method, and a patient and communicative approach. The identified problems were grouped into three categories: (1) instructional issues(monotonous methods, gaps between planning and implementation, limited use of technology), (2) managerial issues (inadequate facilities and infrastructure, low student discipline), and (3) contextual issues (differences in students’ economic backgrounds,limited access (information). This study highlights the need to strengthen the management of school facilities and infrastructure, as well as to develop more diverse classroom management strategies in vocational high schools